Developing and Validating Instrument of Career Decision of Islamic Senior High School Students in Yogyakarta, Indonesia - Arintiya Nadia Arini; Edi Purwanta; Nur Hidayat (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
This study aimed to develop and validate an instrument of career decision of senior high level. Two hundred thirty-three learners from one of the Islamic senior high schools in Yogyakarta were involved in this study. The design of this study was research and development (R&D), which consisted of eight steps: a) identifying the purpose of measuring, b) domain restriction of measuring, c) operationalization of aspects, d) item writing, e) language trial, and field test, f) item selection, g) construct validation, and h) final validation. The researcher implicated students and expert judgments to validate the instrument. A small group and large group instrument try-out were done in this study. To analyze the data, the researcher combined the statistical calculation and confirmatory factor analysis (CFA). The result of this study showed that the career decision instrument undergoes some revision before it was fixed. The expert's judgments & result of the small group try-out showed that the instruments must be improved. The researcher revised some items in the instrument and did the large group try-out. The result of confirmatory factor analysis indicated that the career decision instrument was fixed. It was ready to use by the counseling teachers to help the senior high school students make career decisions for their future.